Agricultural Extension Education in Indonesia in the Colonial Period 1900-1941 (Paramita: Historical Studies Journal, 2020)
This paper examines agricultural extension education during the colonial period in Indonesia and used historical research to investigate it. The agricultural extension was formed in 1911. Agricultural experts in Indonesia at that time were agricultural engineers who graduated from Agricultural College in Wageningen, the Netherlands. They did not understand much about indigenous cultures, languages, and agrarian systems. The task of the agricultural extension was to improve the economy of rural peasant communities. Agricultural education in Indonesia began with the Middlebare Landbouw School for higher education. For lower-level education or the first secondary school, Cultuur School was established. This school prepared graduates to work as forestry officials, agricultural supervisors, and agricultural extension workers. The number of graduates was minimal, so it can not reach the vast territory of Indonesia. For this reason, graduates of agricultural schools who worked in extension offices (Landbouwvoorlichtingsdienst) gave agricultural courses to village school teachers (Vervolksschool). The teachers then taught agriculture to grade five elementary school students, and peasant groups formed in the villages. These peasant groups were led by peasants who have succeeded in the village, which were then used as movers in village economic growth.Tulisan ini membahas pendidikan penyuluhan pertanian selama periode kolonial di Indonesia dan menggunakan menggunakan metode sejarah untuk menelitinya. Penyuluhan pertanian dibentuk pada tahun 1911. Ahli pertanian di Indonesia pada waktu itu adalah insinyur pertanian yang lulus dari Sekolah Tinggi Pertanian di Wageningen, Belanda. Mereka tidak mengerti banyak tentang budaya, bahasa, dan sistem agraria lokal. Tugas penyuluhan pertanian adalah untuk meningkatkan ekonomi masyarakat petani pedesaan. Pendidikan pertanian di Indonesia dimulai dengan Middlebare Landbouw School untuk pendidikan tinggi. Untuk pendidikan tingkat rendah atau sekolah menengah pertama, Cultuur School didirikan. Sekolah ini mempersiapkan lulusan untuk bekerja sebagai pejabat kehutanan, pengawas pertanian, dan penyuluh pertanian. Jumlah lulusannya sangat minim, sehingga tidak bisa menjangkau wilayah Indonesia yang luas. Untuk alasan ini, lulusan sekolah pertanian yang bekerja di kantor penyuluhan (Landbouw voorlichtings dienst) memberikan kursus pertanian kepada guru sekolah desa (Vervolksschool). Para guru kemudian mengajar pertanian ke kelas lima siswa sekolah dasar, dan kelompok tani terbentuk di desa-desa. Kelompok tani ini dipimpin oleh petani yang telah berhasil di desa, yang kemudian digunakan sebagai penggerak dalam pertumbuhan ekonomi desa.